2016
DOI: 10.5603/kp.a2016.0065
|View full text |Cite
|
Sign up to set email alerts
|

Association of monocyte count on admission with angiographic no-reflow after primary percutaneous coronary intervention in patients with ST-segment elevation myocardial infarction

Abstract: A b s t r a c t Background:The no-reflow phenomenon during primary percutaneous coronary intervention (pPCI) in patients with ST-elevation myocardial infarction (STEMI) can lead to poor outcomes. It has been shown that the monocytes may be involved in the pathogenesis of coronary artery disease and associated with high risk of myocardial infarction. Aim:To assess the relation between admission monocyte count and angiographic no-reflow after pPCI. Methods:A total of 236 patients with acute STEMI, who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…In addition, the no-reflow phenomenon is associated with poor long-term prognosis due to post-procedural myocardial infarction [ 8 ]. Although some potential predictors of no-reflow phenomenon have been reported, such as the platelet/lymphocyte ratio and monocyte count [ 9 , 10 ], more predictors are still urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the no-reflow phenomenon is associated with poor long-term prognosis due to post-procedural myocardial infarction [ 8 ]. Although some potential predictors of no-reflow phenomenon have been reported, such as the platelet/lymphocyte ratio and monocyte count [ 9 , 10 ], more predictors are still urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Çelik et al recently demonstrated that female gender, pain to balloon time, high TIMI thrombus grade, tirofiban administration, mean platelet volume, and platelet‐lymphocyte ratio are independent predictors of no‐reflow after primary PCI in young patients. In addition, Wang et al revealed that monocyte count on admission and low hemoglobin concentration are independent clinical predictors of no‐reflow following primary PCI in patients with STEMI. Şahin et al reported that age, DM, acute anterior STEMI, the involvement of left main coronary artery or left anterior descending artery, and thrombus grade are independently associated with no‐reflow in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…In all patients, blood samples for measurements were performed according to our previous work. 3 White blood cell (WBC) count, monocyte count, and other biochemical parameters were drawn into standard ethylenediaminetetraacetic acid (EDTA) containing tubes on admission in the emergency room before the administration of aspirin and clopidogrel. Common blood counting (CBC) parameters were measured by an automated blood cell counter (XS-1000i; Sysmex Co.).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous reports, monocyte counts on admission independently predict no-reflow following primary PPCI. 3 In the current study, we aimed to investigate further the relationship between on admission monocyte count and angiographic intracoronary thrombus burden in patients receiving PPCI.…”
Section: Introductionmentioning
confidence: 99%